2011
DOI: 10.1002/ejoc.201100827
|View full text |Cite
|
Sign up to set email alerts
|

Notably Enhanced Reactivity of the Fulleroid anti‐Bredt Double Bond in Diels–Alder Reactions

Abstract: (3d) and 2-methylbutadiene (3e)] has been carried out in toluene at 30°C. Notably, the relative rate ratio k/k 0 for each dienophile (vs. C 60 ) was remarkably dependent on the diene used; the less hindered H/CN fulleroids 1a and 1b became 25-104 times more reactive than C 60 with conformationally flexible dienes such as 3d and 3e. These fulleroids, however, showed similar or rather diminished reactivity with rigid 3a and 3b. In contrast,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
(48 reference statements)
2
12
0
Order By: Relevance
“…The relative reactivity of the fulleroids vs. C 60 was found to be dependent on the identity of the diene as well as the fulleroid substituent. 30 Pyridyl and phenyl-containing dihydrofuranfused C 60 derivatives were prepared by the base-catalysed or Mn(OAc) 3 -mediated [3+2] cycloaddition reactions of C 60 with the corresponding b-keto esters in high yields. All the new compounds were characterised by elemental analysis and various spectroscopic methods.…”
Section: Production Separation and Properties Of Fullerenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative reactivity of the fulleroids vs. C 60 was found to be dependent on the identity of the diene as well as the fulleroid substituent. 30 Pyridyl and phenyl-containing dihydrofuranfused C 60 derivatives were prepared by the base-catalysed or Mn(OAc) 3 -mediated [3+2] cycloaddition reactions of C 60 with the corresponding b-keto esters in high yields. All the new compounds were characterised by elemental analysis and various spectroscopic methods.…”
Section: Production Separation and Properties Of Fullerenesmentioning
confidence: 99%
“…133 A mixed-valence cluster of cobalt (11) hexacyanoferrate and fullerene C 60 -enzyme-based electrochemical glucose sensor was developed. 134 The preparation and spectroscopic characterisation of the water soluble sodium fullerenolate Na 4 [C 60 (OH) 30 ] has been reported. It has been revealed for the first time that sodium fullerenolate destroys amyloid fibrils of the Ab(1-42) peptide in the brain and prevents their formation in in vitro experiments.…”
Section: Endohedral Fullerenesmentioning
confidence: 99%
“…Fulleroid and azafulleroid have reactive anti‐Bredt olefins at the bridgehead position (Scheme B). The high regioselectivity of them has been reported in hydrogenation, oxidation with singlet oxygen and peracid, Diels–Alder reaction, and 1,3‐dipolar cycloaddition …”
Section: Introductionmentioning
confidence: 99%
“…Material application of the difunctionalized fullerene via the 5,6‐monoadduct has not been well explored except for bisazafulleroid because its regioselectivity depends on the reactants and substituents of fulleroid. For the evaluation of the regioselectivity of 5,6‐bridged monoadduct, our research group previously reported that the reactivity and regioselectivity of Diels–Alder reaction of variously substituted fulleroids with noncyclic and cyclic dienes . Flexible noncyclic dienes such as 2,3‐dimethyl‐1,3‐butadiene (DMBD) showed higher kinetic constants than that of C 60 with high regioselectivity on the bridgehead olefins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation